2020
DOI: 10.1371/journal.pone.0236119
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NPL4 via drug repositioning using disulfiram for the treatment of clear cell renal cell carcinoma

Abstract: The alcohol-abuse drug disulfiram has antitumor effects against diverse cancer types via inhibition of the ubiquitin-proteasome protein nuclear protein localization protein 4 (NPL4). However, the antitumor effects of NPL4 and disulfiram in clear cell renal cell carcinoma (ccRCC) are unclear. Here, we evaluated the therapeutic potential of targeting the ubiquitinproteasome pathway using disulfiram and RNA interference and investigated the mechanisms underlying disulfiram in ccRCC. According to data from The Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Proteasome inhibition activity of DSF was first reported by Lovborg et al (2006) by showing its specific inhibition for 26S proteasome (Lovborg et al, 2006). Combination of DSF or metabolite DDC with Cu has been shown to be a potent inhibitor of the functional proteasomes in many cancers (Kona et al, 2011;Triscott et al, 2012;Brüning and Kast, 2014;Yoshino et al, 2020). Notably, DSF/Cu was shown to inhibit the proteasome activity in breast cancer models but not in normal breast cells.…”
Section: Disulfiram and Proteasome Inhibitionmentioning
confidence: 96%
See 2 more Smart Citations
“…Proteasome inhibition activity of DSF was first reported by Lovborg et al (2006) by showing its specific inhibition for 26S proteasome (Lovborg et al, 2006). Combination of DSF or metabolite DDC with Cu has been shown to be a potent inhibitor of the functional proteasomes in many cancers (Kona et al, 2011;Triscott et al, 2012;Brüning and Kast, 2014;Yoshino et al, 2020). Notably, DSF/Cu was shown to inhibit the proteasome activity in breast cancer models but not in normal breast cells.…”
Section: Disulfiram and Proteasome Inhibitionmentioning
confidence: 96%
“…Reaction between DSF, DDC and Cu results in the generation of extracellular ROS, which in turn induce apoptosis in cancer cells (Lewis et al, 2014;Tawari et al, 2015). It is also demonstrated that the metabolite of DSF, DDC and its copper complex Cu(DDC) 2 get accumulated in the cancer cells and induce ROS generation leading to apoptosis in cancer cells (Guo et al, 2010;Yip et al, 2011;Tawari et al, 2015;Lu et al, 2020;Majera et al, 2020;Yoshino et al, 2020). Generation of both extracellular and intracellular ROS is completely relied on the intact thiol group which chelates copper (Figure 3).…”
Section: Disulfiram-induced Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…If this state lasts longer, it can lead to cell cycle arrest and apoptosis induction [ 37 ]. Moreover, disulfiram offers the potential of a similar mechanism of protein degradation inhibition because, as mentioned above, the CuET complex binding NPL4 cofactor inhibits NPL4, which is involved in the p97-dependent processes, leading to protein degradation [ 53 ].…”
Section: Disulfirammentioning
confidence: 99%
“…Here, we assessed Disulfiram (Antabuse), a well-tolerated alcohol-abuse drug and a promising candidate for repurposing in oncology [ 27 30 ]. In the context of MM, DSF might be particularly interesting because its anticancer activity is related to the CuET metabolite which is spontaneously formed in-vivo and in-vitro in the presence of copper ions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%